Evidence of reduced viremia, pathogenicity and vector competence in a re‐emerging European strain of bluetongue virus serotype 8 in sheep. Issue 3 (22nd February 2019) - Flannery, John; Sanz‐Bernardo, Beatriz; Ashby, Martin; Brown, Hannah; Carpenter, Simon; Cooke, Lyndsay; Corla, Amanda; Frost, Lorraine; Gubbins, Simon; Hicks, Hayley; Qureshi, Mehnaz; Rajko‐Nenow, Paulina; et al.
Summary: The outbreak of bluetongue virus (BTV) serotype 8 (BTV‐8) during 2006–2009 in Europe was the most costly epidemic of the virus in recorded history. In 2015, a BTV‐8 strain re‐emerged in France which has continued to circulate since then. To examine anecdotal reports of reduced pathogenicity and transmission efficiency, we investigated the infection kinetics of a 2007 UK BTV‐8 strain alongside the re‐emerging BTV‐8 strain isolated from France in 2017. Two groups of eight BTV‐naïve British mule sheep were inoculated with 5.75 log10 TCID50 /ml of either BTV‐8 strain. BTV RNA was detected by 2 dpi in both groups with peak viraemia occurring between 5–9 dpi. A significantly greater amount of BTV RNA was detected in sheep infected with the 2007 strain (6.0–8.8 log10 genome copies/ml) than the re‐emerging BTV‐8 strain (2.9–7.9 log10 genome copies/ml). All infected sheep developed BTV‐specific antibodies by 9 dpi. BTV was isolated from 2 dpi to 12 dpi for 2007 BTV‐8‐inoculated sheep and from 5 to 10 dpi for sheep inoculated with the remerging BTV‐8. In Culicoides sonorensis feeding on the sheep over the period 7–12 dpi, vector competence was significantly higher for the 2007 strain than the re‐emerging strain. Both the proportion of animals showing moderate (as opposed to mild or no) clinical disease (6/8 vs. 1/8) and the overall clinical scores (median 5.25 vs. 3) were significantly higher in sheep infected with the 2007 strain, compared to those infected with the re‐emerging strain. However, one sheep infected with the re‐emerging strain was euthanized at 16 dpi having developed severe lameness. This highlights the potential of the re‐emerging BTV‐8 to still cause illness in naïve ruminants with concurrent costs to the livestock industry.